Ability of quantitative PCR to discriminate Pneumocystis jirovecii pneumonia from colonization. Issue 5 (5th May 2020) - Perret, Thomas; Kritikos, Antonios; Hauser, Philippe M.; Guiver, Malcolm; Coste, Alix T.; Jaton, Katia; Lamoth, Frederic
Abstract : Introduction. Pneumocystis jirovecii pneumonia (PCP) is a severe disease affecting immunocompromised patients. Diagnosis is difficult due to the low sensitivity of direct examination and inability to grow the pathogen in culture. Quantitative PCR in bronchoalveolar lavage fluid (BAL) has high sensitivity, but limited specificity for distinguishing PCP from colonization. Aim. To assess the performance of an in-house quantitative PCR to discriminate between PCP and colonization. Methodology. This was a single-centre retrospective study including all patients with a positive PCR result for P. jirovecii in BAL between 2009 and 2017. Irrespective of PCR results, PCP was defined as the presence of host factors and clinical/radiological criteria consistent with PCP and (i) the presence of asci at direct examination of respiratory sample or (ii) anti-PCP treatment initiated with clinical response and absence of alternative diagnosis. Colonization was considered for cases who did not receive anti-PCP therapy with a favourable outcome or an alternative diagnosis. Cases who did not meet the above mentioned criteria were classified as 'undetermined'. Results. Seventy-one patients with positive P. jirovecii PCR were included (90 % non-HIV patients). Cases were classified as follows: 37 PCP, 22 colonization and 12 undetermined. Quantitative PCR values in BAL were significantly higher in patients with PCP versus colonization or undetermined ( P <0.0001). The cut-off of 5×10 3 copies/ml was able to discriminate PCP cases from colonization with 97 % sensitivity, 82 % specificity, 90 % positive predictive value and 95 % negative predictive value. Conclusions. Our quantitative PCR for P. jirovecii in BAL was reliable to distinguish PCP cases from colonization in this predominantly non-HIV population.